Evoked potential studies in the antiphospholipid syndrome: differential diagnosis from multiple sclerosis. Issue 4 (17th August 2005) - Paran, D; Chapman, J; Korczyn, A D; Elkayam, O; Hilkevich, O; Groozman, G B; Levartovsky, D; Litinsky, I; Caspi, D; Segev, Y; Drory, V E
Abstract : Background: The CNS manifestations of the antiphospholipid syndrome (APS) can mimic multiple sclerosis both clinically and radiologically. Objective: To compare evoked potential studies in APS patients and patients with multiple sclerosis with similar neurological disability. Methods: 30 APS patients with CNS manifestations and 33 patients with definite multiple sclerosis and similar neurological disability underwent studies of visual evoked potentials (VEP), somatosensory evoked potentials (SSEP) in the upper and lower limbs (UL, LL), and sympathetic skin responses (SSR) in the upper and lower limbs. Results: The neurological manifestations in the APS patients included stroke (n = 17), transient ischaemic attacks (n = 10), and severe headache with multiple white matter lesions on brain MRI (n = 3). Abnormal SSEP (LL), and SSR (UL; LL) were seen in APS patients (37%, 27%, and 30%, respectively) but VEP and UL SSEP were rarely abnormal (10% and 6%, respectively in APS v 58% and 33% in multiple sclerosis; p = 0.0005, p = 0.008). Mean VEP latencies were more prolonged in multiple sclerosis (116 ms v 101 ms, p<0.001). Only one APS patient had abnormal findings in all three evoked potential studies, compared with seven patients in the multiple sclerosis group (p = 0.04) Conclusions: Abnormal VEPs are uncommon in APS in contrast to multiple sclerosis. Coexisting abnormalities in all other evoked potentials were similarly rare in APS. In patients with brain MRI findings compatible either with multiple sclerosis or APS, normal evoked potential tests, and especially a normal VEP, may support the diagnosis of APS.